SKRINING DAN EDUKASI KESEHATAN TENTANG HIPERTENSI PADA MASYARAKAT - Erni Gustina; Berlianna Septiyaningrum (COVIT (Community Service of Health), 2022)
Hypertension is a public health threat. Hypertension often occurs without complaints so individuals feel that they do not need to have tests to control their blood pressure. This activity aims to provide information to increase public knowledge about hypertension prevention. This activity method uses a community diagnostic approach. Community diagnostics includes data collection, problem identification, problem priority setting, intervention, and evaluation phase. The intervention provided was in the form of health education and educational media in the form of posters about hypertension. The results of the activity showed that the participants were enthusiastic and active in discussions and questions and answers. This activity is expected to increase public knowledge and awareness in efforts to prevent hypertension. Keywords: Hypertension; Media; Prevention; Screening